2015
DOI: 10.1088/1475-7516/2015/12/045
|View full text |Cite
|
Sign up to set email alerts
|

Transition redshift: new constraints from parametric and nonparametric methods

Abstract: In this paper, we use the cosmokinematics approach to study the accelerated expansion of the Universe. This is a model independent approach and depends only on the assumption that the Universe is homogeneous and isotropic and is described by the FRW metric. We parametrize the deceleration parameter, q(z), to constrain the transition redshift (z t ) at which the expansion of the Universe goes from a decelerating to an accelerating phase. We use three different parametrizations of q(z) namely, q I (z) = q 1 + q … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 118 publications
1
21
0
Order By: Relevance
“…Busca et al (2013) gave a value of 0.82 ±0.08. Blake et al (2012) found z trans ≈ 0.7, the same value is also supported by Sutherland & Rothnie (2015) and by Rani et al (2015). The best fit by Vitenti & Penna-Lima (2015) supports a transition redshift z trans ≈ 0.65.…”
Section: The Transition Redshift From Braking To Accelerationsupporting
confidence: 70%
“…Busca et al (2013) gave a value of 0.82 ±0.08. Blake et al (2012) found z trans ≈ 0.7, the same value is also supported by Sutherland & Rothnie (2015) and by Rani et al (2015). The best fit by Vitenti & Penna-Lima (2015) supports a transition redshift z trans ≈ 0.65.…”
Section: The Transition Redshift From Braking To Accelerationsupporting
confidence: 70%
“…Recently, also ref. [75] analysed the age of galaxies, strong lensing and SNe obtaining a constraint on z t < 1, considering both a parametric and a non-parametric approach. Note that previous results were obtained from the analysis of SNe, comprising SNLS and Union2 samples, BAO and from the latest CMB measurements from Planck satellite, while in our case the measurement comes only from cosmic chronometers data and the local H(z) measurement.…”
Section: The Measurement Of the Transition Redshiftmentioning
confidence: 99%
“…Recent studies reveals that the present observed deceleration rate of the Universe is q 0 = −0.51 +0.09 −0.01 [41] and a transition redshift from deceleration to acceleration is z t = 0.65 +0.19 −0.17 [42]. In literature [43][44][45] reported that the Universe passed from a decelerated phase to an accelerated one at z t ≈ 0.7 [46] . So, we have chosen the values of these free parameters (k 1 , k 2 , k 3 , k 4 ) in the present model in such way that our q 0 and z t result are consistent with values reported in the literature.…”
Section: General Solutionmentioning
confidence: 98%